Akbar Djohan Leadership: Strategy and Values in Presenting the Krakatau International Port - Farid Zuhri; Muhammad Faidz Rizqi; Bakhtiar Komarullah; Farid Alghofari (Indonesian Journal of Advanced Research, 2023)
Leadership has better abilities and skills compared to the average employee. Leadership is defined as the process of influencing others to achieve organizational goals, and strategies must consider complex internal and external factors. This research emplo ys the theories of development strategy and transformative leadership using qualitative methodology. M. Akbar Djohan applies modern transformative leadership with an adaptive leadership style at Krakatau International Port, emphasizing progress, openness, consultation, innovation, and creativity in every company project process. He provides motivation and examples that have a significant influence in creating creative solutions and overcoming challenges during the Covid-19 pandemic. The process of adaptation and maintaining effective innovation processes are critical in achieving organizational goals.